Energy management of DC microgrid based on photovoltaic combined with diesel generator, battery and supercapacitor - Han, Shuting (Nanyang Technological University, 2021)
A microgrid that integrates solar photovoltaic (PV), diesel generator (DG), battery and supercapacitor is an economical and environmentally friendly system and it’s suitable for remote area. In this thesis, the off-grid microgrid is studied and the architecture is modeled in MATLAB/Simulink. The HOMER optimization software is used for the economic analysis of the isolated microgrid. The two types of maximum power point tracking (MPPT) algorithms for solar PV are discussed in this report. The P&O and IC MPPT algorithms are applied to control the output power from PV panels. The comparative study of the two MPPT algorithms is are presented. As for the battery-supercapacitor energy storage system, two different control strategies are applied. The different values of voltage control loop compensator gains are studied to analyze its effect on DC link voltage regulation. The stability analysis of the designed controller is also discussed in the dissertation. Also, the stability of the system is tested by varying the AC and DC load, and the simulation results illustrate that the system is steady and can respond to demand change from both AC and DC sides. HOMER software is used to do the optimization and sensitivity analysis. With given data and components value, one optimal system is selected with lowest net present cost (NPC) and levelized cost of energy (LCOE), and the comparative analysis of the optimal system, standalone diesel generator system and the system with all PV, DG and battery is presented.